1983
DOI: 10.1038/ki.1983.191
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on transcellular fluid shifts induced by hemodialysis

Abstract: A computer-based model has been developed to predict the changes in serum sodium, urea concentration, and osmolality as well as transcellular fluid distribution which occur during hemodialysis. Sodium and urea transfers across the dialyzer membrane and transcellular fluid shifts in response to the sodium transfer were modeled assuming that only sodium and its accompanying anions are important as effective osmotic substances in extracellular fluid. Model predictions were consistent with values measured in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 2 publications
2
57
1
1
Order By: Relevance
“…This finding is contrary to predictions derived from mathematical modeling in which RBV is predicted to decrease [6][7][8]. Diffusive dialysis leads to a decreased extracellular osmolarity, as there is an efflux of urea from the extracellular space.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is contrary to predictions derived from mathematical modeling in which RBV is predicted to decrease [6][7][8]. Diffusive dialysis leads to a decreased extracellular osmolarity, as there is an efflux of urea from the extracellular space.…”
Section: Discussioncontrasting
confidence: 56%
“…This could suggest that the hemodynamic instability that occurs during dialysis results from changes in osmolality [3][4][5]. Using kinetic modelling, the rapid fall in the urea concentration of the extracellular compartment is predicted to induce a volume shift from the extracellular to the intracellular compartment [6][7][8]. On the other hand, some studies failed to observe differences in plasma volume preservation between ultrafiltration and ultrafiltration combined with hemodialysis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies by means of volume expansion with hypertonic and hypotonic saline solutions have provided evidence that sodium is functionally distributed in a volume equal to that of TBW [9][10][11]. Furthermore, previous studies have also shown that the product of serum sodium concentration and the intracellular fluid volume is constant in dialysis patients [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Calculations and Statisticsmentioning
confidence: 96%
“…During dialysis, instead, water and sodium removal are closely interrelated since with each liter of ultrafiltrate a fixed quantity of sodium is lost, almost equal to the cation content in the ultrafiltrated plasma. For this reason the sodium concentration of the dialysis fluid plays a key role in adjusting the sodium balance through the diffusive transport from the dialysate to the patient or, more rarely, from the patient to the dialysate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gibbs-Donnan effect) [1,6]. In general, these opposing effects tend to cancel out [22]. Finally, the preparation of the dialysate may lack precision and dialysis machines may not be adequately calibrated.…”
Section: Limitations For the Use Of Sodium Gradient In Clinical Practicementioning
confidence: 99%